Protection of children in Malaysia through foster care legislations and policy - Mohd, Azizah; Abdul Kadir, Nadhilah (2012)
Children are immature, naive and unable to care for themselves. Due to this very nature of children, they are in need of among others, care, attention and supervision from adults. Care, attention and supervision are among the means of care and protection of children, which can only be acquired in a family environment. One of the ways to achieve family environment is through Foster Care where a child who is in need of care and protection will be placed with a family permanently or temporarily or until they are able to care for themselves. Foster care will at least provide for a family life experience especially for children without family or who have problems in their family life. This paper is to examine the Concept of Foster care in Malaysia and the law relating to it as to provide protection to children in need of care and protection. Examination will focus on relevant legislations and policy relating to Foster Care. Discussion will extend to analysis on whether the available laws and policies are adequate to sustain children protection in Malaysia through Foster Care.